Hubungan Penggunaan Kontrasepsi Hormonal dengan Produksi ASI pada Ibu Menyusui - Imelda Altje Rauan; Olvin Manengkey; Michelle Kairupan; Adi Yeremia Mamahit (Jurnal Ilmiah Kesehatan, 2025)
The use of postpartum contraception in Indonesia is still considered suboptimal, even though postpartum contraception improves maternal and infant health by extending birth intervals. The purpose of this study was to analyze the relationship between the use of hormonal contraception and breast milk production in breastfeeding mothers. The type of research is observational analytic with cross-sectional design. The population in this study were all breastfeeding mothers at the Tumpaan Minahasa Selatan Health Center totaling 59 people. The sample in this study was the total population. The results of the study showed that most respondents used hormonal contraception as many as 45 people (76.3%) and respondents who used non-hormonal contraception as many as 14 people (23.7%). Smooth breast milk production was 41 people (69.5%) and those who did not produce breast milk were 18 people (30.5%). The Chi Square statistical test obtained a p-value = 0.003 <0.05. There is a significant relationship between the use of hormonal contraception and breast milk production in breastfeeding mothers. Suggestions from the study are expected that breastfeeding mothers can maintain their psychological condition and use appropriate contraception so that breast milk production will not be disturbed and remain smooth.